Added value of 18F‐florbetaben amyloid PET in the diagnostic workup of most complex patients with dementia in France: A naturalistic study. Issue 3 (26th October 2017) - Ceccaldi, Mathieu; Jonveaux, Thérèse; Verger, Antoine; Krolak‐Salmon, Pierre; Houzard, Claire; Godefroy, Olivier; Shields, Trevor; Perrotin, Audrey; Gismondi, Rossella; Bullich, Santiago; Jovalekic, Aleksandar; Raffa, Nicola; et al.
Abstract: Introduction: Although some studies have previously addressed the clinical impact of amyloid positron emission tomography (PET), none has specifically addressed its selective and hierarchical implementation in relation to cerebrospinal fluid analysis in a naturalistic setting. Methods: This multicenter study was performed at French tertiary memory clinics in patients presenting with most complex clinical situations (i.e., early‐onset, atypical clinical profiles, suspected mixed etiological conditions, unexpected rate of progression), for whom cerebrospinal fluid analysis was indicated but either not feasible or considered as noncontributory (ClinicalTrials.gov : NCT02681172 ). Results: Two hundred five patients were enrolled with evaluable florbetaben PET scans; 64.4% of scans were amyloid positive. PET results led to changed diagnosis and improved confidence in 66.8% and 81.5% of patients, respectively, and altered management in 80.0% of cases. Discussion: High‐level improvement of diagnostic certainty and management is provided by selective and hierarchical implementation of florbetaben PET into current standard practices for the most complex dementia cases. Highlights: Impact of amyloid positron emission tomography (PET) on diagnosis and management in a naturalistic setting. Patients with complex clinical situations in absence of conclusive cerebrospinal fluid results. Highly selected patient population and hierarchical positioning of Alzheimer's disease biomarkers. Use of amyloid PET without interfering with the clinical standard practices. Immediate benefit of amyloid PET in the most complex situations in current practice.